THE NEW ECOLOGY: : IMPACT ON ORGANIZATIONS AND INDIVIDUALS - Cristina Ribeiro Akamine, Suellen (Journal of Interdisciplinary Debates, 2021)
The present study shows that the new organizational ecology is in evidence in the current scenario, requiring investments in practices that aim to produce ecological models to avoid negative impacts on the environment. It is necessary to change the behavior of the individual within organizations and also in society as a whole. We must raise awareness and preserve the environment, avoiding deforestation, fires, pollution generated by industries, unrestrained civil construction, especially in areas of environmental preservation, waste in general, excessive consumption of food of animal origin, disposal trash in inappropriate places, among others. This study was carried out through a literature review on scientific articles. The purpose of this article was to address aspects of the new ecology in the organizational scenario and in individuals. The results observed, through bibliographic studies, were the importance of adopting ecological models in the organizational environment, to avoid negative impacts on the environment, providing a better quality of life for individuals. It was concluded that it is necessary for organizations to adopt measures that preserve the environment, aiming at the welfare and quality of life of society